2011
DOI: 10.1371/journal.pone.0021900
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial RuBisCO Is Required for Efficient Bradyrhizobium/Aeschynomene Symbiosis

Abstract: Rhizobia and legume plants establish symbiotic associations resulting in the formation of organs specialized in nitrogen fixation. In such organs, termed nodules, bacteria differentiate into bacteroids which convert atmospheric nitrogen and supply the plant with organic nitrogen. As a counterpart, bacteroids receive carbon substrates from the plant. This rather simple model of metabolite exchange underlies symbiosis but does not describe the complexity of bacteroids' central metabolism. A previous study using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 41 publications
(45 reference statements)
2
20
0
1
Order By: Relevance
“…4). The grouping based on nifH similarity was well correlated with the grouping based on types of nodulation genes (Table 3), Also, this finding correlated with the ability to fix nitrogen in the free-living state detected from the most of divergent nod-containing strains, which was reported to be restricted among rhizobia to photosynthetic bradyrhizobia (14). Moreover, we found that the A. americana strain SUTN9-2 could nodulate all CI group representatives of Aeschynomene, but ORS285 could nodulate only CI groups 2 and 3.…”
Section: Discussionsupporting
confidence: 54%
“…4). The grouping based on nifH similarity was well correlated with the grouping based on types of nodulation genes (Table 3), Also, this finding correlated with the ability to fix nitrogen in the free-living state detected from the most of divergent nod-containing strains, which was reported to be restricted among rhizobia to photosynthetic bradyrhizobia (14). Moreover, we found that the A. americana strain SUTN9-2 could nodulate all CI group representatives of Aeschynomene, but ORS285 could nodulate only CI groups 2 and 3.…”
Section: Discussionsupporting
confidence: 54%
“…Numerous species of Actinomycetales were reported to be cold adapted and could grow at or below 0°C and were observed in Antarctic soils (Babalola et al 2009). Rhizobiales consisted of Bradyrhizobium, Starkeya, Rhizobium, and Mesorhizobium which were reported to degrade diverse organic matters and are typical symbiotic rhizobia that establish an N 2 -fixing symbiosis with its legume host soybean (Borodina et al 2005;Gourion et al 2011;Singh and Tabita 2010). Burkholderiales consisted of Variovorax paradoxus and Rubrivivax gelatinosus are capable of degrading diverse organic carbons including starch, cellulose, gelatin, chitin, and humic acids (Han et al 2011;Nagashima et al 2012;Satola et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the ability to form nodules without Nod factor, rather than being driven solely by the plants, has also been dependent on a specific single bacterial evolution/mutation (41). The CalvinBenson-Bassham (CBB) cycle from Bradyrhizobium species plays an important role in chemoautotrophic growth (42), and it is important for efficient symbiosis with A. indica (43) by controlling the oxygen tension of the early stage of symbiosis (44). In addition, the ancestors of B. japonicum and A. indica symbionts were photosynthetic free-living bacteria (37).…”
Section: Discussionmentioning
confidence: 99%